Adomas Jakštas - Dambrauskas (1860-1938) as a Lithuanian public figure and literary man - Vanda Stonienė (Knygotyra)
The article deals with the cultural activities of A. Jakštas-Dambrauskas, one of the most prominent Lithuanian personalities at the end of the 19th century and during the first three decades of the 20th century. While still in secondary school, A. Dambrauskas became known as a Lithuanian patriot. As a Catholic priest and public figure, he never accommodated himself to Tsarist policy; he encouraged the Lithuanian youth and priesthood to resist the Tsarist ban on the Lithuanian press and to fight for the right to teach children in the Lithuanian language (for such resistance, he was banished by Russian authorities from his native country for some years).